Five-year relative survival by stage of breast and colon cancers in Italy. Issue 4 (August 2021) - Mangone, Lucia; Mancuso, Pamela; Bisceglia, Isabella; Braghiroli, Barbara; Ferrari, Francesca; Vicentini, Massimo; Giorgi Rossi, Paolo
Objective: To present the changes in 5-year relative survival of patients with breast and colorectal cancer in a northern Italian province in the 2000–2012 period. Changes are presented in relation to stage, period, and age in the screening population. Methods: A total of 5073 breast cancer and 4093 colorectal cancer cases were registered. Breast cancer was divided into 5 age groups: <45, 45–49, 50–69, 70–74 (the target screening population is ages 45–74), and >74 years. Colorectal cancers were classified into 3 age groups: <50, 50–69 (screening target population), and >69 years. Survival was analysed by stage, period, and screening program. Results: Five-year breast cancer relative survival was 92.9% overall, with 100%, 91.9%, 78.8%, 34.2%, and 76.4% for stages I, II, III, IV, and unknown, respectively. Survival increased from 89.7%, 91.8%, and 93.4%, respectively, in the periods 2000–2005, 2006–2009, and 2010–2012. Breast cancer survival was stable in early stages (although already high); a slight improvement was seen for stages III and IV. Five-year colorectal cancer relative survival was 63.6% overall, with 93.3%, 78.6%, 69.8%, 13.2%, and 55.8% for stages I, II, III, IV, and unknown, respectively. No improvement in survival was seen in the periods analysed, although the introduction of screening in 2005 did lead to a sharp decrease in incidence and mortality. Conclusions: For breast cancer, extending the screening target age led to an improvement in survival; for colorectal cancer, the best impact was on incidence and mortality rate.